2016
DOI: 10.1088/0022-3727/49/10/105107
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation and two-photon luminescence from colloidal gold nanoparticles

Abstract: Second harmonic generation and two-photon luminescence from colloidal gold nanoparticles in the 980–1300 nm wavelength range of exciting femtosecond radiation were investigated experimentally. The measured polarization and spectral characteristics of the second harmonic and two-photon luminescence demonstrate that the observed nonlinear optical signal is determined by the dimers constituting several percent of the total nanoparticle number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…HRS intensities, corrected for luminescence contributions, were plotted for each excitation wavelength in order to obtain the full wavelength-dependent HRS response as can be seen in Fig Figure 5a, HRS is enhanced around the LSPR, at 1100 nm ( λ HRS = 550 nm) and is dominated by an increase up to the end of the wavelength range accessible to our set-up (1300 nm, corresponding to 650 nm in HRS) and is most likely due to the presence of a small number of dimers with a red-shifted LSPR due to plasmon coupling (see Figure 7a). [30] The increased error bars in the range from 1250 to 1300 nm in Figure 5 are due to a decrease in signal-to-noise ratio caused by a combined effect of absorption of H 2 O and a lower laser output power. We can observe a small red-shift in the HRS spectrum with respect to the theoretical position of the LSPR (i. e. the peak wavelength in the experimental extinction spectrum).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…HRS intensities, corrected for luminescence contributions, were plotted for each excitation wavelength in order to obtain the full wavelength-dependent HRS response as can be seen in Fig Figure 5a, HRS is enhanced around the LSPR, at 1100 nm ( λ HRS = 550 nm) and is dominated by an increase up to the end of the wavelength range accessible to our set-up (1300 nm, corresponding to 650 nm in HRS) and is most likely due to the presence of a small number of dimers with a red-shifted LSPR due to plasmon coupling (see Figure 7a). [30] The increased error bars in the range from 1250 to 1300 nm in Figure 5 are due to a decrease in signal-to-noise ratio caused by a combined effect of absorption of H 2 O and a lower laser output power. We can observe a small red-shift in the HRS spectrum with respect to the theoretical position of the LSPR (i. e. the peak wavelength in the experimental extinction spectrum).…”
Section: Resultsmentioning
confidence: 96%
“…Wavelength‐dependent HRS of MNPs has been shown before . Although previous studies reported plasmon‐enhanced HRS, the enhancement was only evaluated at one or several excitation wavelengths around the corresponding plasmon band in the linear regime, while the response was probed using a narrow band‐pass filter at half the excitation wavelength .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, a common drawback of TEM is that sample drying, surface interactions, and the powerful electron beam can alter the appearance of the AuNPs with respect to that existing in solution. , Therefore, in situ, solution-based methods are more desirable for looking into the exact mechanism of AuNP growth. Hyper-Rayleigh scattering (HRS), a nonlinear optical (NLO) technique, was proven to be extremely sensitive for probing aggregates of plasmonic particles. We recently showed that plasmon coupling in AuNP aggregates drastically enhances HRS in the near-infrared (NIR) as a result of local field enhancements in the gaps between the detergent-coated AuNPs . Therefore, we hypothesize that the occurrence of aggregation in the initial stages of the classical Turkevich synthesis can indeed be confirmed in situ.…”
Section: Introductionmentioning
confidence: 94%
“…In all four clusters an increase toward longer wavelengths is observed. Such behavior was observed earlier for plasmonic gold nanoparticles and was related to the formation of dimers in solution, but we refrain from concluding that this behavior in our clusters is indicative of plasmon enhancement.…”
mentioning
confidence: 99%